The Oxygen Reduction Activity of Nitrogen-doped Graphene - Jian-feng Liu; Ge Sun; Ting Wang; Kai Ning; Bin-xia Yuan; Wei-guo Pan (Polish Journal of Chemical Technology, 2022)
Graphite nitrogen, pyridine nitrogen and pyrrole nitrogen are the main nitrogen types in nitrogen-doped graphene materials. In order to investigate the mechanism of the oxygen reduction activity of nitrogen-doped graphene, several models of nitrogen-doped graphene with different nitrogen contents and different nitrogen types are developed. The nitrogen content is varied from 1.3 at% to 7.8 at%, and the adsorption energy is calculated according to the established models, then the band gaps are analyzed through the optimization results, so as to compare the magnitude of the conductivity. Finally, the oxygen reduction activity of graphite nitrogen-doped graphene (GNG) is found to be better than pyridine nitrogen-doped graphene (PDNG) and pyrrole nitrogen-doped graphene (PLNG) when the nitrogen content is lower than 2.6 at%, and the oxygen reduction activity of PDNG is the best when the nitrogen content was higher than 2.6 at%.